2017
DOI: 10.1049/iet-rpg.2016.0143
|View full text |Cite
|
Sign up to set email alerts
|

Single‐phase solar PV system with battery and exchange of power in grid‐connected and standalone modes

Abstract: A grid tied photovoltaic (PV) power conversion topology is presented in this study with a novel scheme of resynchronisation to the grid. This scheme serves the purpose of supplying continuous power to the load along with feeding power to the grid. The control approach helps in mitigation of harmonics and improving the power quality while extracting the optimum power from the PV array. Depending on the availability of grid voltage, the proposed configuration is controlled using three approaches, defined as grid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…In reality, however, SUs may operate under a larger set of operating constraints. For instance: chemistry-based batteries may be constrained by internal electrochemical processes [27]; the operation of the SU may be constrained by higher priority applications such as storing energy exclusively for emergency situations [28] or improving power quality [26]. The proposed SU model allows for arbitrary constraints to be embedded in the function h i (·).…”
Section: Constraints In the H I (·) Functionmentioning
confidence: 99%
“…In reality, however, SUs may operate under a larger set of operating constraints. For instance: chemistry-based batteries may be constrained by internal electrochemical processes [27]; the operation of the SU may be constrained by higher priority applications such as storing energy exclusively for emergency situations [28] or improving power quality [26]. The proposed SU model allows for arbitrary constraints to be embedded in the function h i (·).…”
Section: Constraints In the H I (·) Functionmentioning
confidence: 99%
“…3 The extracted heat from the PVT system can be used for space heating, building ventilation, agricultural, industrial materials drying, etc. [22][23][24][25][26] The authors also showed that electrical efficiency decreased by 0.469% for the increase of each degree Celsius of solar cell temperature. Solar thermal collectors along with PV module make a combined form of the PVT system.…”
Section: Introductionmentioning
confidence: 92%
“…The PV module's output power and efficiency reduce if the cell temperature increases. [22][23][24][25][26] The authors also showed that electrical efficiency decreased by 0.469% for the increase of each degree Celsius of solar cell temperature. The authors investigated 13 different types of PV modules in Stuttgart, Germany and Nicosia, Cyprus and found that the variation of temperature coefficient are −0.039%/°C to −0.461%/°C, −0.403%/°C to −0.502%/°C, and −0.353%/°C to −0.456%/°C for amorphous silicon, multicrystalline, and monocrystalline PV cells, respectively.…”
Section: Introductionmentioning
confidence: 92%
“…The battery storage system is integrated with DC bus through the bi-directional converter [10,11] to provide energy back-up. The controller of DC-DC bidirectional converter is shown in Figure 9.…”
Section: Battery Charge Controllermentioning
confidence: 99%